Farmers' perceptions and management of risk in rice/shrimp farming systems in South-West Coastal Bangladesh. (June 2020) - Kabir, Jahangir; Cramb, Rob; Alauddin, Mohammad; Gaydon, Donald S.; Roth, Christian H.
Highlights: Farmers perceived production and market risks. Farmers adopted endogenous and exogenous innovations. Risks were offset by farm and non-farm activities. Rice/shrimp system is economically viable. Research and infrastructure investments are needed to maintain resilience. Abstract: Farmers in Bangladesh face considerable risk due to fluctuations in biophysical and economic conditions, but the response to these risks is poorly understood. In particular, there is a need to better understand the endogenous management of risk in the rice/shrimp farming systems that have emerged in the inner coastal zone of Bangladesh. This paper draws on a case study of a typical rice/shrimp farming village in Khulna District to explore: (a) farmers' perceptions of risks and their management responses, (b) risk-return trade-offs within small-, medium-, and large-farm households, and (c) the role of other farm and non-farm activities in mitigating risks to household livelihoods. Farm-level data were collected through a reconnaissance survey, a village census, household case studies, and a sample survey of 73 households. Representative farm budgets were constructed for the three farm-size classes. The key performance indicators calculated were gross margin (GM), net income (NI), and GM per workday of family labour. The riskiness of the rice/shrimp system was assessed for each farm type using farmers' estimates of low, normal, and high yields and prices to specify triangular distributions. Cumulative distribution functions (CDFs) for GM, NI, and GM per workday were generated. A whole-farm economic analysis was also conducted to assess the relative contributions of different sources of income for each farm type. With access to saline water for shrimp farming in the dry season and fresh water for rice in the wet season, farmers have developed and progressively adapted an alternating rice/shrimp farming system that has minimised the trade-offs between the two crops and provides a good return to household and village resources for all farm types. The system is subject to significant production and market risks, especially the shrimp component. However, farmers have clearly perceived these risks and ameliorated them through a range of production, marketing, and management strategies. With these risk management practices, the rice/shrimp cropping system is economically viable, given the current variation in yields and prices. The greater risk associated with the shrimp component was offset by the renewed stability of the rice component over the past decade, and the risks of the whole cropping system were offset by other farm and non-farm sources of livelihood. Development interventions need to work with farmers to provide further options (suitable rice varieties, solutions to shrimp disease, improved village and transport infrastructure) if this resilience is to be maintained.